ACCEPTANCE AND COMMITMENT THERAPY ISLAMIC APPROACH IMPROVE THE PSYCHOLOGICAL FLEXIBILITY OF PATIENTS WITH MENTAL DISORDERS - Rasmawati (Universitas Islam Negeri Alauddin Makassar, 2022)
Patients with mental disorders experience disturbances in thoughts, feelings, and behavior. They have several psychological problems, such as inadequate emotional regulation and lack of flexibility to adapt to the conditions experienced. One of the psychotherapies that can be used is acceptance and commitment therapy with an Islamic approach. The principle of this therapy is to accept the current condition of having a mental disorder by surrendering to Allah SWT and committing to being more active in achieving healing by endeavoring. This study aims to determine the effect of applying ACT using an Islamic approach on the psychological flexibility of patients with mental disorders. Methods: This research was a quasi-experiment one-group pre-post-test design. This study involved 31 patients with mental disorders treated at the Dadi Hospital in South Sulawesi Province, who were Muslim and had good insight. ACT using the Islamic approach was given in four sessions. The data was collected with a demographic data questionnaire and the Acceptance and Action Questionnaire – II (AAQ-II) and then analyzed using the Paired T-Test with a significance level of < 0.05. Result: The majority of respondents are male (87.1%), unmarried (71%), and working (68.1%). The analysis showed an increase in the psychological flexibility of patients with mental disorders after ACT with an Islamic approach (p-value = <0.001). Conclusion: ACT with an Islamic approach can improve the psychological flexibility of patients with mental disorders, so nurses need to apply ACT as a therapy modality for patients with mental disorders.